Methane and carbon dioxide production from anaerobically incubated boreal peat treated with nitrogen addenda ... - Böhm, Marianne; Baysinger, Mackenzie; Treat, Claire C (PANGAEA, 2025)
This dataset reports greenhouse gas production measurements from a laboratory incubation of sphagnum and peat sourced from a boreal peatland complex (Siikaneva Bog, Finland). Shallow peat samples were extracted in bulk with a bread knife in October 2022 from a homogeneous sphagnum lawn at three locations within several meters distance. Three soil horizons were distinguished according to the position of the water table: above (0-3 cm), fluctuating (3-7 cm) and below the water table (7-20 cm). Three spatial replicates were united per layer. Subsamples from above and below the water table were amended with solutions of NaNO3 and NH4Cl at different concentrations and incubated in 120 ml airtight glass vials in a N2 atmosphere for 365+ days to investigate the effect of nitrogen addenda on greenhouse gas production. Two matching sets of samples were incubated at 4°C and 20°C. Vial containing only untreated water or the treatment solution were kept aside the samples as blanks. The headspace gas was sampled ...